1995
DOI: 10.1111/j.1365-2958.1995.tb02357.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel chromatin‐forming histone H1 homologue is encoded by a dispensable and growth‐regulated gene in Bordetella pertussis

Abstract: We report the identification of a protein homologous to a histone H1 in Bordetella pertussis. The B. pertussis histone homologue, BpH1, varies in size in different strains from 182 to 206 amino acids. The variability of the size of the protein is due to gene variability by insertion or deletion of DNA modules. Insertion of a kanamycin cassette into the bpH1 gene generates a BpH1 null mutant with phenotypic properties and growth rate similar to those of the wild-type strain, showing that this gene is dispensabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Furthermore, this type of regulation is not typical of genes in GAS strain JRS4 either, since we found that the expression of two housekeeping genes, recA and rpsL, remained constant from mid-exponential phase until at least 2 h into stationary phase. The few examples of genes in other bacteria that are expressed only in exponential phase include those encoding small DNA-binding proteins, such as the nucleoid-associated proteins Fis in E. coli and the histone H1 homolog BPH1 in B. pertussis (51,67), genes encoding cell-surface virulence factors in S. aureus (6,29,63), and the regulator abrB in Bacillus subtilis (39,61). The mechanism involved in stationary-phase shutoff has not been completely elucidated in any case, although in S. aureus it involves the complex control network including the regulatory factors Sar, Agr, and Xpr (13,27,55).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this type of regulation is not typical of genes in GAS strain JRS4 either, since we found that the expression of two housekeeping genes, recA and rpsL, remained constant from mid-exponential phase until at least 2 h into stationary phase. The few examples of genes in other bacteria that are expressed only in exponential phase include those encoding small DNA-binding proteins, such as the nucleoid-associated proteins Fis in E. coli and the histone H1 homolog BPH1 in B. pertussis (51,67), genes encoding cell-surface virulence factors in S. aureus (6,29,63), and the regulator abrB in Bacillus subtilis (39,61). The mechanism involved in stationary-phase shutoff has not been completely elucidated in any case, although in S. aureus it involves the complex control network including the regulatory factors Sar, Agr, and Xpr (13,27,55).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 1, several proteins were identified: the BpH1 protein (which migrates with an apparent molecular mass of 30 kDa) described recently by Scarlato et al (29) was eluted at 600 mM NaCl; in addition, two proteins (of approximately 16 and 9 kDa) were eluted at 800 mM NaCl and an 18-kDa protein eluted at 1 M NaCl.…”
Section: Resultsmentioning
confidence: 99%
“…Scarlato et al (29) have described the isolation of BpH1, a histone H1 homolog in B. pertussis, by Southwestern blot techniques; they also detected additional protein bands of lower molecular weights that can also bind to DNA. In order to identify these DNA-binding proteins, crude extracts of B. pertussis 18323 were subjected to affinity chromatography on a heparin-Sepharose column as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal cells, the chromatin found in interphase nuclei contains DNA molecules and nuclear proteins, including histones (4,5,25,(32)(33)(34). The nuclei of interphase cells contain chromatin located within a specific territory or ''domain'' (5,29,31).…”
mentioning
confidence: 99%